Analysis of Symbolic Interaction on Effective Communication of Deaf Student of Darul Ashom Islamic Boarding School Yogyakarta - Khoniq Nur Afiah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2021)
Communication is a primary need for every human being, including people with disabilities. Disability people, such as deaf people, also have interaction patterns to communicate effectively. Effective communication patterns can provide teaching and learning fluently at the Darul Ashom Islamic Boarding School for the Deaf, Yogyakarta. This research aims to study the effective communication design by teachers with deaf students in the Darul Ashom Islamic Boarding School for the Deaf, Yogyakarta. This study uses a qualitative descriptive method with Herbert Blumer’s symbolic interaction analysis perspective. This study indicates that the interaction pattern between deaf students and the teacher uses several symbols in the interaction process, such as spoken language, body language, sign language, and picture symbols. These symbols emerge and are used in the interaction process, especially the teaching and learning technique and memorization. The activities carried out by the students such as Tahsin, memorization, fiqh and hadith studies, murojaah and simaan also illustrate the use of symbolic interactions. The symbolic interaction has a meaning that the communicant and communicator understand to achieve effective communication.